The role of electron-donating subunits in cross-linked BODIPY polymer films - ÖZDEMİR, MÜCAHİT; YALÇIN, BAHATTİN (My University, 2023)
A new method for synthesizing cross-linked 4,4-difluoro-4-bora-3a,4a-diaza-s-indacenes (BODIPYs) using a radical-based thiol-ene click reaction is developed. This method is simple, efficient, and cost-effective, and it produces polymers with unique optical, electrochemical, and surface morphology properties. Significant blue shifts in absorption and photoinduced electron transfer in emissions are observed in the cross-linked BODIPY thin films. Cross-linking also leads to the restriction of conjugation, which results in the breakage of the terminal vinyl group, an increase in the oxidation potential, and a slight upshift in the HOMO position. As a result, the electrochemical band gap is widened from 1.88 to 1.94 eV for polymer bearing N,N-dimethylamino-BODIPY and from 1.97 to 2.02 eV for polymer bearing N,N-diphenylamino-BODIPY moieties. Monomer thin films form planar surfaces due to crystallinity, while amorphous cross-linked BODIPY polymers form more rough surfaces. Additionally, photopatterning on the film surface is successfully performed using different patterned masks. This new method for synthesizing cross-linked BODIPYs has the potential to be used in a variety of applications, including organic electronics, bioimaging, and photocatalysis.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Polimerler ve Plastikler; Fizik Bilimleri; Organik Kimya; Malzeme Kimyası; Polymers and Plastics; Physical Sciences; Organic Chemistry; Materials Chemistry; 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene; electron donating groups; optical properties; photopatterning; surface morphology; thiol-ene click